2023
DOI: 10.3389/fncel.2023.1296235
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of sharp wave-ripples and prevention of network hyperexcitability in the ventral but not the dorsal hippocampus of a rat model of fragile X syndrome

Leonidas J. Leontiadis,
George Trompoukis,
Giota Tsotsokou
et al.

Abstract: Fragile X syndrome (FXS) is a genetic neurodevelopmental disorder characterized by intellectual disability and is related to autism. FXS is caused by mutations of the fragile X messenger ribonucleoprotein 1 gene (Fmr1) and is associated with alterations in neuronal network excitability in several brain areas including hippocampus. The loss of fragile X protein affects brain oscillations, however, the effects of FXS on hippocampal sharp wave-ripples (SWRs), an endogenous hippocampal pattern contributing to memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 185 publications
1
2
0
Order By: Relevance
“…Similarly, I-O curves were similar in WT and KO female DH (F9,326 = 0.034, p = 0.999; WT=15, KO=19; Figure 9C) and VH (F9,214 = 0.639, p = 0.763; WT=15, KO=8; Figure 9D). Regarding male rats, the present results conform with those of a previous study [76]. However, another study reported increased basal excitatory synaptic transmission in the DH of KO vs WT male rats [75].…”
Section: Similar Excitatory Synaptic Transmission In Dh and Vh Of Wt ...supporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, I-O curves were similar in WT and KO female DH (F9,326 = 0.034, p = 0.999; WT=15, KO=19; Figure 9C) and VH (F9,214 = 0.639, p = 0.763; WT=15, KO=8; Figure 9D). Regarding male rats, the present results conform with those of a previous study [76]. However, another study reported increased basal excitatory synaptic transmission in the DH of KO vs WT male rats [75].…”
Section: Similar Excitatory Synaptic Transmission In Dh and Vh Of Wt ...supporting
confidence: 92%
“…For instance, seizures that are a common trait of FXS young individuals [2,91], often involving the anterior hippocampus (that corresponds to the ventral hippocampus in rodents), are absent in adults [2,91,92]. Moreover, the recently shown increase of GABAergic inhibition specifically in the ventral hippocampus of adult KO rats [75,76], the brain region most susceptible to epilepsy [93,94], may represent the result of homeostatic mechanisms activated during the development of individuals with the FXS, in an attempt to compensate for the increased excitability of the brain. Thus, it is tempting to speculate that the normal STSP we found in adult male KO rats may represent the result of adaptive mechanisms that attempt to restore the disrupted STSP in immature KO animals [17,19,21,60].…”
Section: Effects Of Fxs On Stsp and Synaptotagminsmentioning
confidence: 99%
See 1 more Smart Citation